Medieval Iberia readings from Christian, Muslim, and Jewish sources - Constable, Olivia Remie (Middle Ages series, 2012)
For nearly eight centuries, the Iberian peninsula was remarkable for its religious, cultural, linguistic, and ethnic diversity. This expanded second edition of Medieval Iberia brings together original sources that testify to its rich and sometimes volatile mix of Christians, Muslims, and Jews